2004
DOI: 10.1177/08830738040190120501
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intellectual Function After a Unilateral Cortical Lesion: Study of 635 Patients From Infancy to Adulthood

Abstract: This study investigated potential predictors of intellectual outcome in 417 children and 218 adults who had sustained a unilateral cortical lesion. Of these, 295 cases were collected from the scientific literature and 340 from medical records at seven hospitals in Canada Different sets of predictors emerged for the Wechsler Verbal and Performance IQ values, accounting for differing variances (i.e., 12.4% and 20.1%, respectively). The volume of the lesion was the factor that explained the most variance (i.e., 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
(94 reference statements)
1
19
0
Order By: Relevance
“…14 Yet, reported lateralized cognitive deficits after perinatal or childhood stroke are inconsistent, as the outcomes of perinatal stroke are largely dependent on the specific location (cortical, subcortical, or combined) affected structures and lesion severity. 15,43,45 -48 Interestingly, degree of asymmetry accounted for approximately 30% of the variance in cognitive ability observed among study participants. This suggests the relationship between asymmetry of deep medullary vein thrombosis and infarction and cognitive ability needs to be explored further.…”
Section: Discussionmentioning
confidence: 90%
“…14 Yet, reported lateralized cognitive deficits after perinatal or childhood stroke are inconsistent, as the outcomes of perinatal stroke are largely dependent on the specific location (cortical, subcortical, or combined) affected structures and lesion severity. 15,43,45 -48 Interestingly, degree of asymmetry accounted for approximately 30% of the variance in cognitive ability observed among study participants. This suggests the relationship between asymmetry of deep medullary vein thrombosis and infarction and cognitive ability needs to be explored further.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, there was no evidence for the group to systematically "catch up" or "fall behind" over the course of development. This is consistent with findings from some researchers (Montour-Proulx et al, 2004;Westmacott et al, 2010) who found that cognitive outcomes were not related to age at testing;…”
Section: Patterns Of Achievement Across Lesion Variablessupporting
confidence: 92%
“…There have been mixed findings regarding the role of lesion severity on cognitive outcomes, with many studies finding a relationship between larger lesion size and greater impairment (Montour-Proulx et al, 2004;Vargha-Khadem, Isaacs, & Muter, 1994),…”
Section: Patterns Of Achievement Across Lesion Variablesmentioning
confidence: 99%
“…Conversely, it is now well-established that high order cognitive function is indeed modulated by age at lesion onset across the lifespan, particularly the first years of life, and that effect presents itself as an early vulnerability effect [45][46][47][48][49][50][51]. This effect has even been demonstrated with a large sample of brain lesioned children with the same task (c.f., RLAS) as the one used in the present investigation [52].…”
Section: Hypothesesmentioning
confidence: 99%